Efforts to Improve English Language Skills for School Age Children by the Kabuna Village Government, Belu Regency - Seuk Asa, Sefrina Maria; Sae, Donatus (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the government's efforts in Kabuna Village, Kakuluk Mesak District, Belu Regency to develop English language skills for school-age children. Data acquisition techniques in this writing are interviews, observation and library literacy. In the interview method the author uses the snowball technique. Kabuna Village has two English learning groups, namely the English learning group at the village office and in Bautasik Hamlet. The location of this research is an English learning group at the Kabuna and Bautasik Village offices called Bautasik English Speaking (BES). The author conducted interviews with 13 sources consisting of village officials, English teachers and students. BES is located at RT/RW 01/01 Bautasik Hamlet. The aim of BES is to cultivate English for school-aged children with a speaking orientation. The form of activity is speaking practice.